First principles calculation of interfacial stability, energy and electronic properties of SiC/ZrB2 interface. (August 2017) - Xiong, Huihui; Liu, Zhao; Zhang, Henghua; Du, Zheng; Chen, Congmei
Abstract: Interfacial models of SiC/ZrB2 composite coating were studied by first-principles calculations based on density functional theory (DFT). The cubic SiC and hexagonal ZrB2 were selected in our work, and twelve types of SiC (111)/ZrB2 (0001) interface structures were investigated in consideration of four different terminations and three stacking sequences. The cohesive energy ( W ad ), interfacial energy ( γ int ), and electronic structure of the SiC/ZrB2 interfaces were all calculated. The results show that the ZrB2 (0001) surface with 9 layers exhibits bulk-like interior characteristic. Among the interfaces of C/Zr terminated hcp-stacked (CZH), Si/Zr terminated hcp-stacked (SZH), C/B terminated center-stacked (CBC) and Si/B terminated center-stacked (SBT), the CZH interface has the largest W ad (6.28 J/m 2 ) and thus is of the best stability. Over the range of zirconium chemical potential, the γ int of CZH, SZH, CBC and SBT interfaces are −0.31–2.50 J/m 2, 1.07–3.88 J/m 2, 2.85–5.66 J/m 2 and 2.32–5.13 J/m 2, respectively. The calculated electronic properties reveal that, the CZH, CBC and SBT interfaces mainly contain covalent bonding, while the SZH one primarily consists of metallic bonding. Highlights: The interfacial stability, energy and electronic properties of SiC (111)/ZrB2 (0001) interfaces were investigated. For the same termination of ZrB2 /SiC interfaces, the CZH, SZH, CBC and SBT interfaces are considered as the optimal ones. The CZH interface has the strongest adhesion strength and thus has the best stability. The CZH interface mainly consists of strong covalent bonding.